New chimeras and old victimism: Italy’s foreign policy (2008-2018) - Testoni, Michele (Centro Estudios Politicos Constitucionales, 2020)
The article aims to analyze Italy’s foreign policy in the 2008-2018 decade,stressing both its elements of change and its factors of persistence. In this period,Italian politics has undergone a profound,and still unfinished,transformation: from a second republic —a majoritarian democracy dominated by the controversial figure of Silvio Berlusconi— to a third republic,distinguished by the rise of populist,anti-systemic and anti-globalist forces such as the Five Stars Movement and the Northern League. Therefore,one of the most important,and interesting,questions is what kind of relationship exists between the new mechanics of Italy’s political system and the country’s international action. Since any process of change is characterized by the complex and simultaneous interaction of aspects of novelty and continuity,what are the main innovations of Italy’s foreign policy? Above all,what results,in material and symbolic terms,has it achieved? This paper seeks to demonstrate that Italy’s recent foreign relations can be defined by two general phenomena. Firstly,the reap-pearance of two recurring patterns of its diplomatic history: a feeling of frustration in relation to its major allies and the ambition to go back to a policy of «decisive weight» (peso determinante) in the European and the Mediterranean chessboards. Secondly,the permanence of a condition of institutional weakness and unresolved incoherence between the rank and the role of the country in the international arena,a fact that unites both the elites and the public opinion. The conclusion that can be drawn is that,as a consequence of the current process of social fragmentation and polarization,Italy’s foreign policy between 2008 and 2018 has expanded —and not reduced— its characteristics of inadequacy and volatility,thus amplifying its structural ineffective-ness. © 2020,Centro Estudios Politicos Constitucionales. All rights reserved.
[Nuevas quimeras y antiguos victimismos: La política exterior Italiana (2008-2018)]
Keywords: Euro-realism; Euroscepticism; Foreign policy; Geographical ambiguity; Immigration; National identity; Peacekeeping operations; Russia; ODS 16 - Paz, justicia e instituciones sólidas